EXPLORING THE INFLUENCE OF DIGITAL MARKETING ON CONSUMER BEHAVIOR AND LOYALTY - Mukhtar, Shams; A., Chandra Mohan; Chandra, Deepti (International Journal of Research -GRANTHAALAYAH, 2023)
Enterprises have embraced digital marketing as a strategic response to the growing number of consumers on the internet, with the aim of improving their performance. This study aims to deal with the inclinations and reactions of consumers toward a range of digital marketing techniques. The review of existing literature underscores the concept of digital marketing, its capabilities, and the factors influencing consumer conduct, including search engine optimization, intent to purchase, management of customer relationships, buying behavior, satisfaction of customers, and loyalty of customers. Digital marketing encompasses diverse strategies and platforms, such as social media marketing, digital public relations, email marketing, and mobile marketing, which can effectively captivate consumers. The study employs a descriptive research design, obtaining primary data through surveys and in-person interviews. Random sampling is applied, with the participant pool comprising 200 respondents of various ages, genders, educational levels, and occupations. The gathered data is subjected to statistical analysis utilizing techniques like ANOVA and one-sample T-tests. The outcomes show that endorsements from peers and social media platforms significantly impact consumers when making online purchases. Moreover, discounts, rewards, and coupons motivate consumers to review online. Interaction and customization are pivotal drivers for cultivating and sustaining enduring consumer relationships. Marketing professionals should harness digital media and social platforms to facilitate effective communication, augmenting customer satisfaction and loyalty. This inquiry augments comprehension of consumer preferences and reactions to digital marketing tactics.